ARTICLE APPLICATION PAPER 4 - Alexander, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The fourth set of readings centers around two questions. First, "How does consumption serve to reproduce and maintain class boundaries?" In other words, consumption acts as a sign (signifies) one’s socioeconomic class and serves to keep a social hierarchy in place. Veblen talks about "Conspicuous consumption" and "conspicuous leisure" as visible signs of inequality. Holt discusses Bourdieu’s concept of "cultural capital" and taste differences between people with higher or lower cultural capital. The other set of readings center on the question, "How is commodification, as a system, spreading to other areas of social life?" Everything is becoming a commodity for sale – politicians, religion, education, "values" (e.g. family values or environmental values), childhood, sports, pets, etc…). Marx, the father of all discussions of consumption, identifies how a commodity gets its "value." Finally, Gladwell looks at how "coolhunters" seek out the hottest items in order to mass produce the items back to a consumer.Please select ONE of the questions below